Always connected? Examining the impact of constant connectivity on employee well-being in Indonesia - Anna Partina; Sri Astutik; Nikodemus Hans Setiadi Wijaya; Luis Diego Lee (Jurnal Manajemen dan Pemasaran Jasa, 2026)
This study aims to test the antecedents of constant connectivity, specifically the visibility of colleagues and supervisors, as well as its consequences in the form of employee well-being. Furthermore, the study examines the mediating role of psychological detachment in the relationship between constant connectivity and its consequences. The data were obtained from 207 valid responses from employees across food and beverage, banking, education, and retail companies in Indonesia, encompassing both operational and administrative roles. The collected data were examined using the Warp PLS analytical tool. The findings indicate that the visibility of colleagues’ and supervisors’ communication through mobile work devices (MWDs) positively influences constant connectivity. Whereas constant connectivity does not affect employee well-being and psychological detachment. Meanwhile, psychological detachment affects employee well-being and mediates the relationship between constant connectivity and employee well-being. This study offers a contribution by demonstrating that constant connectivity is not merely a technological by product but is socially constructed through patterns of interpersonal visibility within organizations. Nevertheless, this study is subject to certain limitations. By using self-report questionnaires, this study may raise concerns regarding common method bias. Future research are encouraged to employ longitudinal designs to more effectively capture how constant connectivity unfolds over time and how psychological detachment fluctuates across work and non-work periods.